Physicians' preferences for information sources : a meta-analytic study - HAUG, J. D (Bulletin of the Medical Library Association, 1997)
Identification of the resources physicians use to acquire information for clinical practice and medical research is an important area of research for health sciences librarianship and medical practice. During the past twenty years several studies have addressed questions about physicians' preferences for information sources, but generalization from the results of these studies has been hampered by limited sampling, diverse methods, and varied reportorial formats. Meta-analysis provides a method for reducing these limits. Using a meta-analytic procedure, this study reviews twelve studies published between 1978 and 1992, categorizes and ranks the physicians' preferred information sources reported in each study, then aggregates and counts the frequencies of the top six preferences, as well as the associated first and second preferences, for all the study populations or their strata. The results indicate that physicians prefer to obtain information from journals and books, but also that they often consult colleagues to get answers to clinical and research questions. The implications of these findings for health sciences librarianship are briefly discussed.